**Note:- 1) If y = x^n ; then dy/dx = n*{x^(n-1)}**

**2) If y = secx ; then dy/dx = secx*tanx**

Now,

f(x) = y = 1/[{1+secx}^2] = {1+secx}^(-2)

thus, dy/dx = f'(x) = y' = (-2)*[{1+secx}^(-3)]*(secx*tanx)

or, dy/dx = f'(x) = y' = (-2*secx*tanx)/[{1+secx}^(3)]

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now